2019
DOI: 10.1001/jamainternmed.2018.7661
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Inclusion of Studies Identified by the FDA as Having Falsified Data in the Results of Meta-analyses

Abstract: This article was corrected on November 23, 2020, to fix results of mistakenly included analyses and coding errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…For example, 3 guidelines and 15 reviews in the radiation oncology literature have been reported to cite retracted articles as valid sources of data (Zietman et al 2019). One recent study (Garmendia et al 2019) had found that nearly half of 24 meta-analyses including falsi ed data of clinical trials had conclusions altered if excluded the awed results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 3 guidelines and 15 reviews in the radiation oncology literature have been reported to cite retracted articles as valid sources of data (Zietman et al 2019). One recent study (Garmendia et al 2019) had found that nearly half of 24 meta-analyses including falsi ed data of clinical trials had conclusions altered if excluded the awed results.…”
Section: Discussionmentioning
confidence: 99%
“…The mass production of such summarizing data collections contributes significantly to the dissemination and survival of false data. Garmenia and coworkers [7] found that 46% of all re-assessed meta-analyses would result in a change in the initial findings if studies with falsified data were to be excluded. The authors concluded that "Falsified data can affect not only the original publication, but also any subsequent meta-analyses and any resulting clinical or policy changes resulting from the findings of these studies."…”
Section: Thomas Stammmentioning
confidence: 99%
“…The authors concluded that "Falsified data can affect not only the original publication, but also any subsequent meta-analyses and any resulting clinical or policy changes resulting from the findings of these studies." [7].…”
Section: Thomas Stammmentioning
confidence: 99%
“…A recent study examined the impact that a clinical trial that contained falsified data had on 22 meta-analyses that included it, and concluded that 10 (46%) metaanalyses had their results significantly changed [15]. This result, however, cannot be generalised due to various limitations.…”
Section: Bodymentioning
confidence: 99%